Markers of psychoemotional maladaptation under wartime stress - Korshunova, Марія; Khaustova, Олена (Psychosomatic Medicine and General Practice, 2026)
Background. Chronic combat stress during wartime leads to systemic depletion of adaptive resources in military personnel, manifested by specific psychophysiological and stress-related maladaptation, as well as dysregulation of the autonomic nervous system (ANS). The need to objectively assess these conditions, which often extend beyond standard psychiatric nosologies, highlights the importance of an integrated analysis of physiological markers and subjective bodily experience. Objective. To improve the accuracy of multidimensional psychological assessment and psychotherapeutic interventions in military personnel through the evaluation of autonomic nervous system (ANS) functioning using heart rate variability (HRV) markers of stress-related maladaptation, as well as through the investigation of interoceptive awareness and resilience, including their interrelationships and nosological specificity. Materials and methods. The study included 48 male military personnel (mean age 39.7 ± 7.6 years). The investigation was based on instrumental ECG analysis (time-domain, spectral, and nonlinear HRV parameters) combined with a psychodiagnostic assessment battery including MAIA-2 (interoception), BPQ-SF (body perception and autonomic reactivity), and CD-RISC-10 (resilience). Statistical analysis included descriptive statistics, frequency distribution analysis, Pearson correlation analysis, and one-way analysis of variance (ANOVA). Results. The study identified a state of psychophysiological maladaptation characterized by a systemic reduction in HRV indices (SDNN 29.12 ± 17.46 ms; RMSSD 19.93 ± 13.27 ms; HF 129.91 ± 172.84 ms²) compared with population norms, indicating pronounced suppression of vagal control. The sample structure demonstrated a predominance of low HRV levels with a complete absence of high HRV values, emphasizing the widespread nature of autonomic dysfunction. HRV parameters demonstrated high internal physiological consistency, while heart rate (HR) showed significant inverse correlations with SDNN and RMSSD, indicating a substantial reduction in autonomic flexibility with increasing cardiovascular strain. Interoceptive analysis revealed a deficit in adaptive awareness according to MAIA-2. In addition, a moderate positive correlation was found between SD1/SD2 and the “Body Listening” subscale (r = 0.40), whereas HF demonstrated a negative correlation with the MAIA “Noticing” subscale (r = −0.33), reflecting hypervigilant and anxiety-related perception of bodily signals. Resilience was significantly reduced and demonstrated stable inverse associations with autonomic symptomatology. Importantly, subgroup analysis excluding participants with cardiovascular pathology did not alter the correlation structure, confirming the stability of the identified psychophysiological model. One-way ANOVA revealed no statistically significant differences in HRV parameters (p > 0.05) among PTSD, anxiety-depressive, and psychotic disorder groups, suggesting a transdiagnostic nature of autonomic maladaptation under chronic combat stress. Discussion. The findings allow the condition of military personnel to be interpreted through the model of “disintegrated interoception,” in which bodily signals are perceived intensely but cease to function as stabilizing resources due to suppression of the ventral vagal complex. The absence of nosological specificity in HRV suggests that prolonged stress establishes a functional state in which the organism remains trapped in continuous mobilization regardless of the specific diagnosis. This highlights the role of HRV not as a biomarker of specific disorders, but as a general indicator of the depth of maladaptation and self-regulatory exhaustion. Conclusions. HRV may be considered an integral marker of psychophysiological maladaptation. Combined assessment of autonomic regulation, interoception, and resilience appears promising for the early identification of maladaptation and for planning rehabilitation interventions. Keywords: heart rate variability, stress-related maladaptation, military personnel, interoceptive awareness, resilience, autonomic nervous system, chronic stress.